Mind the Gap: Destabilizing Dominant Discourses and Beliefs about Learning Disabilities in a Bachelor of Education Program - Iannacci, Luigi; Graham, Bente (Alberta Journal of Educational Research, 2010)
This study explores teacher candidates’ understandings of children with special needs and learning disabilities; the effect of a special education course supporting a tutoring practicum; and how curricula can critically deconstruct and disrupt dominant, inequitable notions and practices. Data were collected through initial and end-of-course questionnaires and focus groups that took place after the course and related practica had ended. Theory-practice gaps addressed are transferable to teacher education contexts where the focus is on developing future teachers’ understandings of and responses to dis/ability in early childhood education learning environments.